Inclusion Properties on a Class of Meromorphic Functions Defined by a Linear Operator - Firas Ghanim; Maslina Darus (Journal of Mathematical and Fundamental Sciences, 2016)
In the present paper, we study a certain class of meromorphic univalent functions f(z) dened by the linear operator L(Î±,Î²) f (z). The aim of the present paper is to prove some properties for the class Î£Î±,Î²,kÎ»;(h) to satisfy the certain subordination.AMS Subject Classication: 30C45